Pengaruh Penggunaan Bahasa Gaul Dikalangan Siswa Terhadap Penggunaan Bahasa Indonesia Di SMK Negeri 10 Medan - Adelina Sitanggang; Bertania Permata Sari; Fahrysyah Aulya; Mira Cahya Hendra; Kurnia Pulungan (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research aims to determine the phenomenon that occurs in the students' environment when using slang becomes a habit and daily language and the impact on students at SMK Negeri 10 Medan by not using good and correct Indonesian. The sample sampling in this mini research is students who use slang and are not good at speaking Indonesian well and describe the characteristics of the research population. This type of research is qualitative, namely a qualitative data analysis method that clarifies situations experienced in everyday life. The results of this research can be concluded that the existence of slang is certainly very detrimental to the existence of the Indonesian language. They found that slang can be used comfortably among them. This is considered to be a characteristic that differentiates it from other groups among students.